Are teachers missing the beat on students’ motor competence? - Fábio Flôres; Joana Serpa; Fernando Vieira; André Pombo; Denise Soares; Dimitar Shabanliyski; Rita Cordovil (PLoS ONE, 2026)
Purpose Compare physical education (PE) teachers’ perceptions of their students’ motor competence (MC) with students’ objectively assessed actual motor competence. Methods 20 PE teachers and 340 students participated. Teachers were asked to estimate the student MC. Normative videos of the performance on each test (Standing Long Jump, Shuttle Run, Shifting Platforms, Jumping Sideways, Ball Throwing, and Kicking Velocity) were presented to assess teachers’ perceptions of MC. Paired t-tests with Cohen’s d quantified differences between children’s actual motor competence and teachers’ perceptions, alongside error tendency analyses (accurate, over-, or underestimation) using a 5% threshold. Associations and agreement between perceived and actual MC were examined using Pearson correlations and Bland-Altman plots. Findings Teachers overestimated MC in most tests, particularly stability-related tasks such as the Shifting Platforms test (p < 0.001). However, underestimations were evident in the Standing Long Jump test (p < 0.001), where students performed above national values. Also, there was a tendency to underestimate the lateral jumps, but it was not significant. Conclusion Our findings underscore the need for targeted teacher training programs and curriculum adjustments to improve assessment accuracy, ensuring that PE instruction effectively promotes skill development.